PENGARUH MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) TERHADAP PENCAPAIAN KOMPETENSI IPA SISWA KELAS VIII SMP NEGERI 1 SUNGAI LASI KABUPATEN SOLOK - Bivalia Audina; Asrul Asrul; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2016)
Back ground of this research are  low motivated student in science and they are competences are not satisfafied. Some reason is the lack of understanding and interest of students in science lessons is students do not dare to ask and receive only what is explained by the teacher. One alternative used to overcome this problem is to implement a learning model ARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction) that are expected to generate confidence and interest of the students so that arouse the curiosity of the subject matter. The research objective is  to investigate the effect in scince  learning model ARIAS of student  of  class VIII  SMP Negeri 1 Sungai Lasi District Solok. Type of research is quasi-experimental research with the design of Randomized Control Group Only Design. The  population in research is  all students of class VIII SMP Negeri 1 Sungai Lasi listed in the Academic Year 2015/2016. Sampling was done by cluster random sampling technique. Samples were VIII.3 class as a class experiment with the number of students 20 and VIII.2 class as a class controls the number of students 18 people. The research data covers three competencies are competence of knowledge, attitude, and skills. The research instrument are achievement test for competency knowledge, observation sheets  for attitude competence, and performance assessment sheets for competency skills. Data were analyzed using t-test on the real level of 0.05. Data for the competence of knowledge, attitudes, and skills of both classes of normally distributed samples and having variances  homogenity, so do test the equality of two average by t-test. From the are  calculation results obtained tcount for knowledge competencies, namely 2.15, ie 1.83 competency attitudes, skills and competencies is 3.22 with a value table = 2.02. So it can be concluded that the value of the t-test knowledge and skills competency is outside the reception Ho while competencies are in the attitude of the reception area of Ho. The relationship between the learning model ARIAS to learning outcomes competences kwnoledge r= 0,74. Based on the results of hypothesis testing can be concluded that there is a significant impact on the application of learning models ARIAS (Assurance, Relevance, Interest, Assessment, statisfaction) towards the attainment of IPA in the aspects of knowledge and skills, but not in the aspect of the attitude student  of class VIII  of SMP Negeri 1 Sungai Lasi District Solok